2021
DOI: 10.1111/odi.13996
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis OG1RF induces apoptosis in MG63 cells via caspase‐3/‐8/‐9 without activation of caspase‐1/GSDMD

Abstract: Objective Regulated cell death is key in the pathogenesis of persistent apical periodontitis. Here, we investigated the mechanisms of regulated cell death in osteoblast‐like MG63 cells infected with Enterococcus faecalis OG1RF. Materials and methods MG63 cells were infected with live E. faecalis OG1RF at the indicated multiplicity of infection for the indicated infection time. We evaluated the cells by flow cytometry, terminal deoxynucleotidyl transferase dUTP nick end labelling assay and lactate dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…In the present study, E. faecalis infection increased the number of TUNEL-positive cells and apoptotic cells in the early and late phases, which was also observed in our previous study on MC3T3-E1 and MG63 cells infected with E. faecalis [10,12]. We also noticed that necrotic cells of which the cell membrane integrity is damaged may also be stained as Annexin V-FITC/PI double-positive, as previous studies reported [29,30].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, E. faecalis infection increased the number of TUNEL-positive cells and apoptotic cells in the early and late phases, which was also observed in our previous study on MC3T3-E1 and MG63 cells infected with E. faecalis [10,12]. We also noticed that necrotic cells of which the cell membrane integrity is damaged may also be stained as Annexin V-FITC/PI double-positive, as previous studies reported [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Hence, it is crucial to examine the role of E. faecalis on osteoblast apoptosis in PAP. Our previous study found that E. faecalis strains from the root canals of teeth with PAP trigger apoptosis in mouse MC3TE-E1 and human MG63 cell lines [10,12]. However, the effect of E. faecalis on apoptosis in human primary osteoblasts and its mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations